Academic freedom : autonomy, challenges and conformation - Ceglie, Robert; Thompson, Sherwood (Emerald Publishing Limited, 2021)
Framed in the context of a world in which academic freedom is often jeopardized, or criticized by outside social forces, Academic Freedom: Autonomy, Challenges and Conformation sets out to echo the voices of faculty who have encountered challenges to academic freedom within their personal and professional careers. Including chapters which range from showcasing specific experiences within particular disciplines, to providing broad historical or philosophical perspectives, this edited collection provides an authentic account of how academic freedom has helped and hindered the academic profession, scholarship, and teaching. Revealing one-on-one interactions which shed light on the views of individual educators, this book shifts focus onto the day-to-day ramifications of limited academic freedom. Faculty members recollect occasions where they have experienced a challenge to their ability to exchange ideas and concepts freely in the classroom, to explore and disseminate new knowledge, and to speak professionally and privately on topics in their field of expertise without being under duress. Offering up a finely curated collection of chapters, editors Ceglie and Thompson allow readers to understand the dynamic between academic freedom and professional responsibilities, and also open up an opportunity to discuss challenges to academic freedom and the potential loss of autonomy in higher education in the United States and beyond.
Includes index.
Keywords: Academic freedom.; Education, Philosophy, Theory & Social Aspects.; Philosophy & theory of education.; elektronické knihy; electronic books